Prospects of Estimating Poverty with Phone Surveys : Experimental Results from Serbia - Boznic, Vladan; Katayama, Roy; Munoz, Rodrigo; Takamatsu, Shinya; Yoshida, Nobuo (World Bank, Washington, DC, 2017)
Telephone surveys enable us to collect data in a cost-effective and timely manner, but may not be conducive for collecting detailed consumption or income data for measuring poverty due to the required length of the interview and complexity of the questions. Combining telephone surveys with a survey-to-survey imputation technique may be a solution, as this technique can produce reliable poverty estimates from only 10 to 20 simple questions. However, this approach may lead to biased results if the interview mode, that is, face-to-face versus telephone interviews, affects how households respond to questions. By conducting the first survey experiment to examine potential differences in poverty estimates between interview modes, this study finds that the reporting patterns changed very little between the two interview modes, and the bias in poverty estimates due to interview mode is statistically insignificant. These findings suggest that poverty monitoring via telephone surveys is promising, but additional experiments in other country contexts are encouraged.